Changes in enzymatic activity of the arable soil layer under different systems of primary tillage and fertilization of typical chernozem in the short crop rotation of the right-bank forest-steppe zone of Ukraine - Prymak, I.; Panchenko, O.; Fedorchuk, M.; Yeremenko, Oksana; Єременко, Оксана Анатоліївна; Еременко, Оксана Анатольевна; Panchenko, Ihor (My University, 2019)
The highest activity of invertase, urease, phosphatase, dehydrogenase and polyphenol oxidase in the arable layer of typical chernozem was observed when applying a moldboard -subsurface tillage in the crop rotation, the lowest-under a shallow disk tillage. The highest protease activity was in the moldboard tillage, peroxidase-in the beardless tillage, and catalase-in the disk tillage, while the lowest correspondent indices were recorded in the permanent shallow (10-12 cm), moldboard and differentiated tillage in the crop rotation. Phosphatase activity of the arable layer did not differ significantly between the beardless and disk tillage. Indices of the peroxidase activity were almost at the same level for the chisel and differentiated tillage. Localization of plant remains and organic fertilizers in the upper soil layer in the beardless and disk tillage leads to the increasing activity of enzymes. The highest coefficient of humus accumulation was recorded in the moldboard-beardless, the lowest-in the disk tillage. Fertilizers raise the soil enzymatic activity. A differentiated system of primary tillage in the crop rotation is recommended, which includes plowing to a depth of 25-27 cm for the sunflower, beardless tillage for the maize and soybeans (25-27 and 16-18 cm, respectively) and shallow (10-12 cm) tillage by a disk harrow for the rest of crops in the rotation. It is proposed to use 12 tons of manure+N95P82K72 per one hectare of the arable land
Keywords: enzymes; soil; tillage; fertilizers; crop rotation; humus; productivity